It is the business model… Reframing the problems of UK retail banking. (January 2017) - Froud, Julie; Tischer, Daniel; Williams, Karel
Abstract: This paper introduces and applies the concept of critical business model analysis to explore dysfunctional behaviour in the UK retail banking sector and to outline possible policy approaches. The paper starts from the conventional micro-economic framing of banking as the outcome of insufficiently competitive markets, yet after two decades of policy responses the sector is not only more concentrated but also homogeneous, dominated by financialized organisations focused on sustaining high rates of return on equity. Critical business model analysis is used to reframe the banking sector as one based on mimetic behaviours, including mis-selling of financial products and opaque charging. In doing so, the paper contributes to the public debate on the reform of retail banking by highlighting the potential importance of a wider diversity of business models within the sector as a way of offering customers a different choice and limiting the scope of financialized practices.